2004
DOI: 10.1186/1471-2156-5-7
|View full text |Cite
|
Sign up to set email alerts
|

A new set of BXD recombinant inbred lines from advanced intercross populations in mice

Abstract: Background: Recombinant inbred (RI) strains are an important resource for mapping complex traits in many species. While large RI panels are available for Arabidopsis, maize, C. elegans, and Drosophila, mouse RI panels typically consist of fewer than 30 lines. This is a severe constraint on the power and precision of mapping efforts and greatly hampers analysis of epistatic interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
236
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(243 citation statements)
references
References 44 publications
(29 reference statements)
2
236
0
Order By: Relevance
“…In addition to the differential performance of B6 and D2 mice on tasks assessing the rewarding properties of psychostimulants, studies using these strains have shown gene-by-environment interactions on the propensity to self administer cocaine as a function of housing condition and maternal environment (van der Veen et al 2007(van der Veen et al , 2008 and amphetamine-induced conditioned place preference as a function of a brief period of food shortage (Cabib et al 2000). Finally, the B6 and the D2 strains are the progenitor strains for the BXD recombinant inbred (RI) panel, of which the BXD20 and BXD86 strains are part (Peirce et al 2004;Taylor et al 1977Taylor et al , 1999Williams et al 2001). The BXD RI panel has frequently been used to map complex polygenic traits (Chesler et al 2003;Philip et al 2010) including those directly related to the DA system (Boone et al 2008;Janowsky et al 2001;Jones et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the differential performance of B6 and D2 mice on tasks assessing the rewarding properties of psychostimulants, studies using these strains have shown gene-by-environment interactions on the propensity to self administer cocaine as a function of housing condition and maternal environment (van der Veen et al 2007(van der Veen et al , 2008 and amphetamine-induced conditioned place preference as a function of a brief period of food shortage (Cabib et al 2000). Finally, the B6 and the D2 strains are the progenitor strains for the BXD recombinant inbred (RI) panel, of which the BXD20 and BXD86 strains are part (Peirce et al 2004;Taylor et al 1977Taylor et al , 1999Williams et al 2001). The BXD RI panel has frequently been used to map complex polygenic traits (Chesler et al 2003;Philip et al 2010) including those directly related to the DA system (Boone et al 2008;Janowsky et al 2001;Jones et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic reference panels of mice exist (Peirce et al 2004;Williams et al 2004;Grubb et al 2009;Bennett et al 2010). The latest is the Collaborative Cross (CC), a large panel of recombinant inbred lines derived from a genetically diverse set of eight inbred mouse strains (A/J, C57BL/6J, 129S1/SvImJ, NOD/LtJ, NZO/HiLtJ, CAST/EiJ, PWK/PhJ, and WSB/ EiJ).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Several such panels have been or are being developed for a variety of species, including yeast, Drosophila (Ayroles et al 2009), Arabidopsis (Kover et al 2009), maize (Buckler et al 2009), Caenorhabditis elegans ( Johnson and Wood 1982;Li et al 2006;Rockman and Kruglyak 2009), and mice (Chesler et al 2008;Iraqi et al 2008;Morahan et al 2008). Efforts are also being made to expand (Peirce et al 2004) and maximize the potential of existing populations (Bennett et al 2010). In the construction of these populations, there is a unique opportunity to observe the impact of selection and inbreeding depression on the range of phenotypic diversity and genetic structure (Ayroles et al 2009;Rockman and Kruglyak 2009).…”
mentioning
confidence: 99%